Breaking the cycle of mass atrocities: criminological and socio-legal approaches in international criminal law - Aksenova, Marina; Sliedregt, Elies van; Parmentier, Stephan (Hart, 2019)
Intro -- Acknowledgements -- Contents -- List of Contributors -- List of Cases -- PART I: CYCLE OF MASS ATROCITIES -- 1. Introduction: Breaking the Cycle of Mass Atrocities: Criminological and Socio-Legal Approaches to International Criminal Law -- I. The Cycle of Mass Atrocities -- II. Structure of the Book -- III. Methodological Approach -- IV. Urgency in Developing Multidisciplinary Approaches to International Criminal Law -- 2. The Biology and Psychology of Atrocity and the Erasure of Memory -- I. The Search for Criminological Understanding: The Criminology of Atrocity and Confronting the 'Monster Within' -- II. A Framework for Discussion: It Begins in Biology But Includes Much Else -- III. Memory and the Erasure of Memory -- IV. Sign-Off -- PART II: CRIMINALISATION -- 3. International Criminalisation as a Pragmatic Institutional Process: The Cases of Dominic Ongwen at the International Criminal Court and Thomas Kwoyelo at the International Crimes Division in the Situation in Uganda -- I. Introduction -- II. Beyond the 'Black Letter' Origin of International Criminalisation -- III. Pragmatic Criminalisation as a Dual-Nature Institutional Process -- IV. International Criminalisation as a Pragmatic Institution-Dependent Process in the Situation in Uganda -- V. Conclusions -- 4. Solidarity as a Moral and Legal Basis for Crimes Against Humanity: A Durkheimian Perspective -- I. Introduction -- II. Reasons for Looking at Durkheim in 'Grounding' International Criminal Law -- III. Problems with the Category of Crimes Against Humanity -- IV. The 'How' Question: International Criminal Trials as Religious Rituals -- V. Conclusion: The Rising Significance of the Category of Crimes Against Humanity -- PART III: TRIAL AND PUNISHMENT -- 5. The Hybrid System of International Criminal Law: A Work in Progress or Just a Noble Experiment? -- I. Introduction.